Charge transfer complexation boosts molecular conductance through Fermi level pinning. Issue 8 (10th January 2019) - Wang, Kun; Vezzoli, Andrea; Grace, Iain M.; McLaughlin, Maeve; Nichols, Richard J.; Xu, Bingqian; Lambert, Colin J.; Higgins, Simon J.
Abstract : Efficient charge transport across long molecular wires enabled by charge-transfer complexation, through Fermi level pinning of interference features. Abstract : Interference features in the transmission spectra can dominate charge transport in metal–molecule–metal junctions when they occur close to the contact Fermi energy ( E F ). Here, we show that by forming a charge-transfer complex with tetracyanoethylene (TCNE) we can introduce new constructive interference features in the transmission profile of electron-rich, thiophene-based molecular wires that almost coincide with E F . Complexation can result in a large enhancement of junction conductance, with very efficient charge transport even at relatively large molecular lengths. For instance, we report a conductance of 10 −3 G 0 (∼78 nS) for the ∼2 nm long α-quaterthiophene:TCNE complex, almost two orders of magnitude higher than the conductance of the bare molecular wire. As the conductance of the complexes is remarkably independent of features such as the molecular backbone and the nature of the contacts to the electrodes, our results strongly suggest that the interference features are consistently pinned near to the Fermi energy of the metallic leads. Theoretical studies indicate that the semi-occupied nature of the charge-transfer orbital is not only important in giving rise to the latter effect, but also could result in spin-dependent transport for the charge-transfer complexes. These results therefore present a simple yet effective way to increase charge transport efficiency in long and poorly conductive molecular wires, with important repercussions in single-entity thermoelectronics and spintronics.